Expression and Roles of Antimicrobial Peptides in Innate Defense of Airway Mucosa: Potential Implication in Cystic Fibrosis - Geitani, Regina; Moubareck, Carole Ayoub; Xu, Zhengzhong; Karam Sarkis, Dolla; Touqui, Lhousseine (Frontiers in Immunology, 2020)
Respiratory infections are nowadays associated with complicated treatments due to the dissemination of antibiotic resistance in the community and clinical settings. Development of new antibiotics is notoriously costly and slow; therefore, alternative strategies are needed. Antimicrobial peptides (AMPs), central effector molecules of the immune system, are being considered as alternatives to conventional antibiotics. Most of AMPs are epithelium-derived and play a key role in host defense at mucosal surfaces. They are classified on the basis of their structure and amino acid motifs. These peptides display a range of activities, including not only direct antimicrobial activity, but also immunomodulation and wound repair. In the lung, airway epithelial cells and neutrophils in particular contribute to AMPs synthesis. The relevance of AMPs for host defense against infection has been demonstrated in animal models and is supported by observations in patient studies, showing altered expression and/or unfavorable circumstances for their action in a variety of lung diseases. Of note, AMPs are active against bacterial strains that are resistant to conventional antibiotics, including multidrug-resistant bacteria. Several strategies have been proposed to use these peptides in the treatment of infections, including direct administration of AMPs. In this review, we will focus on studies related to direct bactericidal effects of AMPs and their potential clinical applications, with a particular focus on cystic fibrosis.